Ubiquity of Rotational Symmetry Breaking in Superconducting Films, From Fe(Te,Se)/Bi2Te3 to Nb, and the Effect of Measurement Geometry - Debarghya Mallick; Hee Taek Yi; Xiaoyu Yuan; Seongshik Oh (Advanced Science)
Abstract FeTe0.5Se0.5/Bi2Te3 heterostructure is a promising new platform in the journey toward topological quantum computation, considering that first, FeTe0.5Se0.5 (FTS) is itself known to be a topological superconductor (TSC) and second, the heterostructure has topological interface states that can be proximitized into TSC even if FTS fails to become TSC on its own. Here, it is shown that this system exhibits quasi‐2D superconductivity, and utilizing the standard in‐plane magneto‐transport measurements, two‐fold anisotropy (a.k.a nematicity) is discovered in longitudinal resistance (Rxx) and critical current (Ic) measurements, even though the system exhibits globally 12‐fold symmetry. Then, similar measurements are carried out on a polycrystalline niobium (Nb) thin film, a well‐known s‐wave elemental superconductor, and a similar two‐fold symmetry is found even for this Nb system. This implies either that nematic behavior is ubiquitous or that the in‐plane magneto‐transport measurement scheme routinely used to detect nematicity, is not a reliable method to probe nematicity. It is shown that the angle‐dependent response of vortices in the superconducting regime to the magnetic Lorentz force is very likely the main cause behind the ubiquitous nematic behaviors of this measurement scheme. In other words, this measurement scheme is intrinsically two‐fold, and is therefore not suitable to detect the nematicity. Accordingly, all the previous reports of nematicity based on similar measurement practices, reported on various samples, including thin films, bulk crystals, and exfoliated flakes, need to be reinterpreted.